Multi-objective optimization of an on-road bicycle frame by uniform design and compromise programming - Cheng, Yung-Chang; Lee, Cheng-Kang; Tsai, Ming-Tsang (Advances in mechanical engineering, 2016)
With the rapid changes in manufacturing technology of bicycle, the safety and performance of a bicycle are important and remarkable research subjects. In this study, an innovative and integrated optimization procedure for multi-objective optimization of an on-road bicycle frame is presented. The multiple objectives are to reduce the bicycle frame’s permanent deformations and to decrease the bicycle frame’s mass. First, uniform design of experiments is applied to create a set of sampling points in the design space of control factors. Second, three-dimensional solid models of bicycle frames are constructed and permanent deformations of bicycle frames under dropping-mass and dropping-frame impact test simulations are measured by ANSYS and ANSYS/LS-DYNA. Third, Kriging interpolation is used to transform the discrete relations between input control factors and output measures to continuous surrogate models. Fourth, compromise programming and mixture uniform design of experiments are used to integrate the multiple-objective functions into one compromise objective function. Finally, generalized reduced gradient algorithm is employed to solve the optimization problem. After executing the innovative optimization procedure, an optimized on-road bicycle frame is obtained. Comparing with the original design, the frame’s permanent deformations and mass are reduced. Therefore, both consolidation and lightweight of on-road bicycle frame are achieved.